Love Poems - Ronnie, Purple; Illustrations by Cornin, Janet and Andreae, Giles (London Boxtree, 2000)
Purple Ronnie's unique style of humour has made him the favourite poet of love-struck romantics and horny heart-throbs everywhere.
Include Illustration
Keywords: Love poetry, English -- Bawdy poetry -- Erotic poetry, English